2002
DOI: 10.1176/jnp.14.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Depression and Parkinson's Disease on Cognitive Functioning

Abstract: This study compared the performance of Parkinson's disease (PD) patients with and without depression, patients with depression alone, and normal control subjects on a cognitive screening instrument, the Mattis Dementia Rating Scale (DRS) to evaluate the influences of depression and Parkinson's disease on cognition. PD affects overall level of cognitive functioning and, to a lesser extent, DRS Initiation/Perseveration, Construction, and Attention. Diminished memory was primarily related to depression. Treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 26 publications
0
23
1
2
Order By: Relevance
“…Several studies have demonstrated an association between depression and cognitive impairments in PD patients [22][23][24][25][26][27][28][29][30]. There are, however, a few other studies that did not detect a significant association between depression and variance in cognitive deficit in PD (See table 1) [31][32][33][34].…”
Section: Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated an association between depression and cognitive impairments in PD patients [22][23][24][25][26][27][28][29][30]. There are, however, a few other studies that did not detect a significant association between depression and variance in cognitive deficit in PD (See table 1) [31][32][33][34].…”
Section: Depressionmentioning
confidence: 99%
“…Letter Fluency, Abstract Reasoning and Card Sorting Test [22], Category Fluency Test and TMT [29], setshifting and response inhibition [40], Frontal Assessment Battery and Stroop test [27]. As for deficits in other cognitive domains, earlier studies have reported an association between depression and poorer scores on tasks of attention (assessed by a subtest of the Dementia Rating Scale and Digit Span Forward) [25,26], short-term memory (measured by Digit Span Forward and Backward) [30], and memory which was assessed by the Word-list recall and recognition test [22], Hopkins Verbal Learning Test [24,41], a subtest of the Dementia Rating Scale [26] and the Pattern Recognition Memory Task [29]. In addition, another study indicated a relationship between depression and poorer performance on a range of cognitive tasks including those testing executive function (Trail Making Test), memory (Rey Auditory Verbal Learning Test) and visuospatial skills (Rey-Osterreith Complex Figure Test) [42].…”
Section: Depressionmentioning
confidence: 99%
“…Difficulties with memory, attention, and language are also common in PD and are frequently aggravated by depression [8,59,60,61,62]. This widespread cognitive impairment has been noted despite the absence of clinically significant cognitive decline [8].…”
Section: Expert Commentary Unique Features Of Dpdmentioning
confidence: 99%
“…Blazer & Williams, 1980 ;Griffiths et al 1987 ;Austin et al 2001 ;Norman et al 2002). Nearly all have compared normal elderly against psychiatric patients or individuals whose self-report scores indicate risk of clinically significant depression.…”
Section: Introductionmentioning
confidence: 99%